The brand of Hungary: why (not)? - Braun, Róbert (The Hungarian Journal of Marketing and Management, 2019)
Nation or place branding is a popular theme now. Most everyone thinks that a strong nation brand can help a country flourish. Building upon current literature of destination branding the paper argues that nation brands became so complex that newly designed nation brands have lost their power of differentiation. Taking the argument further it argues that the case of Hungary is an unique one. The paper claims that having started too late and witnessing special problems of transition societies the social, political, and cultural pre-requisites of a branding exercise are not present. Therefore the paper argues that instead of a stong nation brand even stronger local brands, regions, cities, clusters are needed and may be designed.